Prevalence of work related musculoskeletal disorders (WMSDs) and ergonomic risk assessment among readymade garment workers of Bangladesh: A cross sectional study - Hossain, Mohammad Didar; Aftab, Afzal; Al Imam, Mahmudul Hassan; Mahmud, Ilias; Chowdhury, Imran Ahmed; Kabir, Razin Iqbal; Sarker, Malabika (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2018 Hossain et al. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal. pone.0200122 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0200122